2005
DOI: 10.1152/physiol.00029.2004
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Microparticles: Two Sides of the Coin

Abstract: Microparticles are plasma membrane-derived vesicles shed from stimulated cells, in the broad sense of the term. Their presence is interpreted by proximal or remote cells in fundamental physiological processes including intercellular communication, hemostasis, and immunity. On the other hand, variations of their number or characteristics are frequently observed in pathophysiological situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
565
0
15

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 591 publications
(587 citation statements)
references
References 46 publications
7
565
0
15
Order By: Relevance
“…Furthermore, it has been recently shown that cells may transiently modify the phenotype of neighboring cells by transferring surface receptors, intracellular proteins, and mRNA in mechanisms that involve exchange of cell-membrane-derived microvesicles (Ratajczak et al, 2006a,b). Shedding of membrane-derived microvesicles is a physiological phenom-enon that accompanies cell growth and cell activation, for example, hypoxia or oxidative injury (Beaudoin and Grondin, 1991;VanWijk et al, 2003;Morel et al, 2004;Hugel et al, 2005 -galactosidase).…”
Section: Bm-derived Stem Cells and Tissue/organ Regeneration: Evidencmentioning
confidence: 99%
“…Furthermore, it has been recently shown that cells may transiently modify the phenotype of neighboring cells by transferring surface receptors, intracellular proteins, and mRNA in mechanisms that involve exchange of cell-membrane-derived microvesicles (Ratajczak et al, 2006a,b). Shedding of membrane-derived microvesicles is a physiological phenom-enon that accompanies cell growth and cell activation, for example, hypoxia or oxidative injury (Beaudoin and Grondin, 1991;VanWijk et al, 2003;Morel et al, 2004;Hugel et al, 2005 -galactosidase).…”
Section: Bm-derived Stem Cells and Tissue/organ Regeneration: Evidencmentioning
confidence: 99%
“…In addition, extracellular vesicles including exosomes and microparticles (MPs) are emerging as novel vectors for cell–cell communication [12,13]. MPs are small plasma membrane-derived vesicles with a diameter of 100–1000 nm which carry a variety of proteins, lipids, mRNA and miRNA arising from the cell of origin [13,14]. MPs have been implicated in a host of physiological and pathological processes.…”
Section: Introductionmentioning
confidence: 99%
“…During the process the cells also release phosphatidylserine (PS)-positive membrane fractions called microparticles (MPs). Activated platelets and MPs actively participate in the promulgation of atherosclerosis and related diseases, pathologies of the central nervous system and neoplasia [6].…”
Section: Introductionmentioning
confidence: 99%